LANSKAP LINGUISTIK DI TAMAN LITERASI MARTHA CHRISTINA TIAHAHU, JAKARTA SELATAN - Indrastuti, Suryani; Munawarah, Sri (Multikultura, 2025)
Taman Literasi Martha Christina Tiahahu (TLMCT) is a tourist attraction located in South Jakarta that has been established since 1948. As a tourist attraction, TLMCT has signages and facility markers to facilitate visitors to find and utilize the facilities at the park. Those signs use code preference, inscription, and emplacement to maximize the information delivery. The formulation of the problem in this research is how the code preference, inscription, and emplacement of linguistic landscape (LL) at TLMCT. This research aims to explain the code preference, inscription, and emplacement of LL at TLMCT. Quantitative and qualitative methods were used in this research. The LL data were analyzed using Spolsky and Cooper’s (1991) taxonomy of sign functions and Scollon and Scollon’s (2003) place semiotics theory. The results of the analysis show that a total of 118 LL at TLMCT has four functions, which are informative signs, warning notices and prohibitions, commemorative plaques, and advertising signs. Meanwhile, the code preference used in LL at TLMCT shows the attitude of prioritizing Indonesian language. In terms of inscription, LL at TLMCT use a variety of materials that indicate the period of the LL use. The colours used in LL make the LL enhance readability and reflect TLMCT’s colour identity. Almost all LL were placed in locations appropriate to their context. Linguistically, LL at TLMCT has sufficiently fulfilled Indonesian language rules; nevertheless, there are some mistakes in the LL that need to be corrected.